Efektifitas Zakat Produktif Dalam Meningkatkan Perekonomian UMKM dengan Pendekatan Zakat Core Principle (ZCP) Studi pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Sorong - Sri Fatimah; Surahman Amin; Nur Faizah (Prodi Ekonomi Syariah IAIN Sorong, 2022)
The purpose of this study is to explain the facts in the field to determine the effectiveness of the distribution of zakat funds and also how the distribution of zakat funds in Baznas, sorong regency. The method used is a qualitative method. The data collection in this study using direct interviews with related parties Baznas Sorong Regency end also the recipients of productive zakat. The second is by means of documentation techniques in the from of financial statements in 2021. The research result obtained that zakat is productive in improving the economy of. It is appropriate that productive zakat is zakat given to sameone who is used as working capital. The from of distribution in Baznas Sorong Regency is the productive zakat program in the from of individual capital business assitence. Secondly, the effectiveness of productive zakat in improving economy during the covid-19 pandemic with the zakat core priinciples (ZCP) approach, there are two categories, namely the calculation of disbursement collection ratio (DRC) and the speed of time. The calculation according to the DRC in 2021 is 73% so that is included in the effective DRC category. The speed off time in the productive program, the time required at the time of distribution is 7 month. It can be concluded that the national amil zakat agency (Baznas) of sorong regency has distributed effectively in 2021 both in terms of the DRC ratio with the effective category and the speed of distribution time in the category